Debt Covenant, Political Cost, Political Connection, And Bank Connections Towards Company Value - Yuliana; Agus Munandar (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
The goal of this study is to look at how debt covenant, political cost, political connection, and bank connections affect company value. The research used secondary data with completed financial reports from 24 public companies or 120 data in the banking sector that met purposive sampling criteria over five years (2017 to 2021). The research found that debt covenant and bank holder connection (the second form of bank connection) have a negative effect on company value. Meanwhile, political cost, political association and shareholder connection (the third form of bank connection) positively impact company value. At the same time, executive connection (the first bank connection) did not affect company value. At the same time, it was discovered that debt covenant, political cost, political connections, and three types of bank connections all impacted company value.